RE-IMAGINING EMPLOYEE ENGAGEMENT WITH CHANGING TIMES : A QUALITATIVE PERSPECTIVE - Ms. Antriksha Negi,; Mr. Ravinder Pant,; Prof. Nawal Kishor, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
An engaged workforce is a key to organizational success. Currently engagement is seen as another core competitive advantage for any organization and top management has shown a great interest in engaging their employees to retain talent in the organization as well as to improve satisfaction of employees along with service of clients. According to a report published by Forbes, employees, who do not feel engaged are more likely to resign from their jobs and highly engaged workforce is more likely to remain committed and motivated towards their employer. Contribution of Service Sector in India in terms of GDP at current prices is estimated to be Rs. 92.26 lakh crore in the year 2018-19, accounting for 54.40% of total GDP India as per the statistics issued by Ministry of Statistics and Programme Implementation (2018-2019). Management needs to acquire the understanding of factors driving engagement levels in their organization. The study aims to identify antecedents of employee engagement in current scenario with special reference to service sector by undertaking thorough review of literature and interviewing the HR managers. The antecedents derived are skill variety, feedback and autonomy (Bakker & Demerouti, 2008), Perceive Supervisory Support (Byrne, Peters, & Weston, 2016), (Zhong, 2016) , rewards and recognition, concern for employees, sense of ownership and social engagements etc.